Ritual, media, and conflict - Grimes, Ronald L.; Hüsken, Ute; Simon, Udo Gerald (Oxford ritual studies series, 2011)
Here, an interdisciplinary team of 24 scholars locates describes, and explores cases in which media-driven rituals or ritually saturated media instigate, disseminate, or escalate conflict. Each chapter, built around global and local examples of ritualized, mediatized conflict, is multi-authored.